CLINICAL SAFETY OF ZAFIRLUKAST TREATMENT DURING ACUTE INFLAMMATORY REACTION IN NILE TILAPIA (OREOCHROMIS NILOTICUS) - ARACATI, M. F.; RODRIGUES, L. F.; OLIVEIRA, S. L.; MORAES, A. C.; PRADO, E. J. R.; FERNANDES, D. C.; ETO, S. F.; SILVA, I. C.; BELO, M. A. A. (Ars Veterinaria, 2021)
Little is known about the toxicity of immune modulators in fish. Zafirlukast is an anti-inflammatory that antagonizes cysteine leukotriene receptors (CysLTR1). Aiming to develop strategies for the sanitary management of fish farms, this study evaluated the clinical safety of oral zafirlukast treatment, through biochemical and hematological analyzes during acute inflammatory reaction in Nile tilapia (Oreochromis niloticus), induced by Aeromonas hydrophila bacterins. 72 young tilapias were randomly divided in 9 aquariums (100 L each, n=8) to compose the following treatments: T0 (control), T1 (Treatment with 250 µg zafirlukast) and T2 (Treatment with 500 µg zafirlukast). Eight animals were evaluated per treatment in three periods: six, 24 and 48 hours post-inoculation (HPI), blood collection was performed for hematological and serum biochemical evaluation. The study of hepatic and renal functionality revealed that treatment with both doses of zafirlukast did not result in changes in the circulating values of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase, creatinine, triglycerides, cholesterol, and total protein, suggesting that the drug has not compromised liver and kidney functions. Tilapia submitted to treatment with 500 µg showed adverse hematological effects characterized by polycythemia associated with microcytosis and hypochromia. Therefore, oral treatment with zafirlukast has demonstrated clinical safety at a therapeutic dose of 250 µg in tilapia during acute aerocystitis, although hematological changes were observed in tilapia treated with overdose of this leukotriene blocker.